Revisiting moral panics - Cree, Viviene E. 1954-; Clapton, Gary 1948-; Smith, Mark 1950- (The Policy Press, 2015)
Drawing on the popular Economic Social and Research Council (ESRC) seminar series, this book examines social issues and anxieties, and the solutions to them, through the concept of moral panic